Socioeconomic inequality in self-reported unmet need for oral health services in adults aged 50 years and over in China, Ghana, and India - Alexander Kailembo; Raman Preet; Jennifer Stewart Williams (BMC, 2018)
Abstract Background The 2015 Global Burden of Disease Study estimated that oral conditions affect 3.5 billion people worldwide with a higher burden among older adults and those who are socially and economically disadvantaged. Studies of inequalities in the use of oral health services by those in need have been conducted in high-income countries but evidence from low- and middle-income countries (LMICs) is limited. This study measures and describes socioeconomic inequality in self-reported unmet need for oral health services in adults aged 50 years and over, in China, Ghana and India. Methods A cross-sectional analysis of national survey data from the WHO SAGE Wave 1 (2007-2010) was conducted. Study samples in China (n = 1591), Ghana (n = 425) and India (n = 1307) were conditioned on self-reported need for oral health services in the previous 12 months. The binary dependent variable, unmet need for oral health services, was derived from questions about self-reported need and service use. Prevalence was estimated by country. Unmet need was measured and compared in terms of relative levels of education and household wealth. The methods were logistic regression and the relative index of inequality (RII). Models were adjusted for age, sex, area of residence, marital status, work status and self-rated health. Results The prevalence of unmet need was 60, 80, and 62% in China, Ghana and India respectively. The adjusted RII for education was statistically significant for China (1.5, 95% CI:1.2-1.9), Ghana (1.4, 95% CI: 1.1-1.7), and India (1.5, 95% CI:1.2-2.0), whereas the adjusted RII for wealth was significant only in Ghana (1.3, 95% CI:1.1-1.6). Male sex was significantly associated with self-reported unmet need for oral health services in India. Conclusions Given rapid population ageing, further evidence of socioeconomic inequalities in unmet need for oral health services by older adults in LMICs is needed to inform policies to mitigate inequalities in the availability of oral health services. Oral health is a universal public health issue requiring attention and action on multiple levels and across the public private divide.